Morphological variations of weedy rice (Oryza sativa ssp.) in selected rice fields of Peninsular Malaysia - Muhamad Safwan Ishak,; Noraziyah Abd Aziz Shamsudin,; Ismail Sahid,; Khairiatul Mardiana Jansar, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Weedy rice or locally known as ‘padi angin’ has been infesting rice granary areas in Malaysia for the last 20 years. The outbreak of weedy rice in the country started during the late 1980s in Projek Barat Laut Selangor (PBLS) due to the adoption of direct-seeding practices. Weedy rice can be characterized by its early maturing and easy-shattering traits. The objective of this study was to determine the morphological variations of weedy rice in selected granary areas located in Peninsular Malaysia. A total of 110 weedy rice accessions were collected from nine locations in three granary areas in Peninsular Malaysia (the Western, Eastern, & Northern regions). The collected weedy rice accessions were planted under greenhouse conditions to study their morphological features. Results of the present study indicated that 73.6% of weedy rice accessions were awnless while the remaining 26.4% produced awn. Selected traits such as plant height, flag leaf length, culm length, number of tillers, number of panicles, and panicle length were included in the Principal Component Analysis (PCA). The weedy rice accessions were grouped into three different clusters mainly Cluster 1: cultivated rice and awnless populations, Cluster 2: brown and red pericarp awnless populations, and Cluster 3: awned populations. The findings of this study may be used as guidance for farmers and researchers for designing sustainable weedy rice management in the future.